Suspected nasopharyngeal carcinoma in three workers with long-term exposure to sulphuric acid vapour. Issue 6 (1st June 1999) - Ho, C K; Lo, W C; Huang, P H; Wu, M T; Christiani, D C; Lin, C T
Abstract : Sulphuric acid vapour has been suspected of being an industrial carcinogen. In this study, a cluster is presented of three patients with nasopharyngeal carcinoma (NPC) who worked in the same building of a telecommunications conveyance station in southern Taiwan with long term exposure to sulphuric acid vapour concentrations as high as 0.18 mg/m3. All three workers were diagnosed with NPC within a 5 month period between September 1992, and March 1993. Compared with 19 other healthy workers from the same building, these three workers with NPC had worked significantly longer in this building than had the others (mean (SD) (years): 12.7 (0.6) v 7.4 (4.4); p = 0.01). With an in situ nucleic acid hybridisation and immunostaining method for colocalised Epstein-Barr virus (EBV) and secretory component (SC) protein among biopsy specimens of these three patients with NPCs, it was found that some tumour cells did not contain EBV and SC protein staining signals. These results indicate that EBV infection is not the only risk factor for NPC and long term exposure to relatively low concentrations of sulphuric acid vapour may be associated with the development of NPC.